Characterization of the diversity, genomic features, host bacteria, and distribution of crAss-like phages in the pig gut microbiome - Wang, Yaxiang; Wei, Chao; Chen, Zhe; Zhou, Mengqing; Huang, Lusheng; Chen, Congying (Frontiers in Veterinary Science, 2025)
Phages play an important role in shaping the gut microbiome. CrAss-like phages, which are key members of the gut virome, show high abundance in the human gut and have attracted increasing interest. However, few studies have been found in pigs, and the distribution of crAss-like phages across broader pig populations remains unknown. Here, we obtained 1,251 pig crAss-like phage genomes from 403 metagenomes publicly available and a pig gut virome dataset constructed by ourselves. These crAss-like phage genomes were further clustered into 533 virus operational taxonomic units (vOTUs). Phylogenetic analysis revealed that crAss-like phages in pig guts were distributed across four well-known family-level clusters (Alpha, Beta, Zeta, and Delta) but were absent in the Gamma and Epsilon clusters. Genomic structure analysis identified 149 pig crAss-like phage vOTUs that utilize alternative genetic codes. Gene blocks encoding replication and assembly proteins varied across crAss-like phage clusters. Approximately 64.73% of crAss-like phage genes lacked functional annotations, highlighting a gap in understanding their functional potential. Numerous anti-CRISPR protein genes were identified in crAss-like phage genomes, and CAZymes encoded by these phages were primarily lysozymes. Host prediction indicated that bacterial hosts of pig crAss-like phages primarily belonged to Prevotella, Parabacteroides, and UBA4372. We observed that interactions between crAss-like phages and Prevotella copri might have a possible effect on fat deposition in pigs. Finally, all detected vOTUs exhibited low prevalence across pig populations, suggesting heterogeneity in crAss-like phage compositions. This study provides key resources and novel insights for investigating crAss-like phage-bacteria interactions and benefits research on the effects of crAss-like phages on pig health and production traits.